Kompetensi Aparatur Dalam Pelayanan Publik di Dinas Kependudukan Dan Catatan Sipil Kota Gorontalo - Tamaun, Witarti; Dance Tui, Fenti Prihatini; Tantu, Romy (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aimed to discover the characteristics of (1) Character. (2) Motive. (3) Attitude. (4) Knowledge and (5) Skills of officers in public services at the Department of Population and Civil Registration of Gorontalo City. This study was conducted using descriptive qualitative. The data were collected using observation, interviews and documentation. Furthermore, the data was analyzed using data collection, reduction, display, and drawing conclusions or verification. He study results showed that the character characteristics, motives, attitudes, knowledge and skills of officials in public services at the Department of Population and Civil Registration of Gorontalo City were quite good. However, the knowledge and skills still need continuous improvement to provide better services to the community. The characteristics of apparatus knowledge still need to be improved further, either through training, outreach, or other efforts. Increasing apparatus knowledge can provide benefits such as better service, process efficiency, and increased community satisfaction. The characteristics of the technical skills of the apparatus were not evenly distributed. It showed differences in the level of mastery of technical skills between officers. Younge’r people familiar with technology can easily operate the system and manage files digitally.